Les marqueurs de changement de topique du discours en roumain : évolution sémantique et rôle pragmatique - Alice Ionescu; Cecilia-Mihaela Popescu (Discours)
This paper attempts to describe how adverbs and adverbial expressions of manner and space came to function as discourse markers of topic shifting in contemporary Romanian and to sketch a possible typology of these markers. We have analyzed the following units, which can function as topic shift markers: altfel (“otherwise”), de altfel (“besides”), de asemenea (“moreover”), (de) altminteri (“otherwise”, “moreover”), pe de altă parte (“on the other hand”, “from another point of view”), în altă ordine de idei (“on a different note”) and apropo (“by the way”). Like most pragmatic markers in the Romance languages, these units are polyfunctional, as they are able to combine several discursive and modal functions at the discourse level. They contribute to the orientation of the discourse topic, while expressing an argumentative stance. Our analysis will take the etymology of the aforementioned markers and their semantic and pragmatic evolution as a starting point, in order to explain the appearance, in certain contexts, of their pragmatic value of markers of topic shifting (i.e., their pragmaticalisation). Our arguments will be illustrated by examples drawn from a corpus of literary texts (provided by the textual databases of Romanian Archeus.ro, CORV [Corpus de română vorbită] and IVLRA [Interacţiunea verbală în limba română actuală]) as well as written and spoken language samples taken from the web using the Google search engine or Reverso and Linguee online dictionaries.